PENGARUH SARI KURMA PADA IBU POSTPARTUM TERHADAP BERAT BADAN BAYI DI BPM PIPIN HERIYANTI YOGYAKARTA - Dwi Yulinda (Universitas Jenderal Achmad Yani Yogyakarta, 2018)
Background: Galactogogues is one of pharmaticeutical agents to support the initiation, continuation or augmentatiton of breast milk product. Natural product of galactogogues contenst such as palm fruits. So many puerpural mother prefer using natural galactogogues to help incerase their milk supply is in observing successive measurment of the infant’s naked weight. Nearly all infants lose weight for the first two to four days after birth. Postnatal weight loss on regaining birth weight are cliical parameters for monitoring an infat feeding status in the first week. Objective: This study aimed to assess the effect of date palm fruits on postpartum to infant weight Methods: Research was conducted on maternal postpartum which is divided into two groups. They are the control group; and the treatment group which was given dates palm fruit. Infant weight was measured at 7 day after birth. The analytical method used is Student T-test. Results: Date Palm fruits increased infant weight which was significantly on firstweek increase in the treatment group compared to the control group at p <0.05. Conclusion: Date Palm fruits is one of the alternatives that can be done to prevent infant lose weight. Keywords: Date palm fruit, postpartum, infant weight